An assessment of e-document retrieval services in Turkey's medical libraries - Güneş, Güssün; Çolaklar, Huriye (My University, 2013)
Electronic resources, particularly electronic databases, electronic articles, and electronic documents, are among the foremost resources used in making scientific information accessible to library users. Libraries and health institutions in Turkey have inevitably joined in a cooperative effort to facilitate the process of accessing medical information. Medical libraries are in cooperation with each other in providing information services and accessing articles in national and international publications. These joint efforts not only encompass systems in individual libraries but also facilitate document retrieval on the basis of a national network. ULAKBİM’s TÜBESS and ANKOS’s KİTS can be cited as two examples of these nation-wide document retrieval systems. The objective of the present study has been to obtain information on electronic retrieval services in medical libraries, a practice that has a direct impact on the quality of clinical and scientific research in Turkey. The study comprises a subject-based statistical analysis of e-journal types and article request figures for e-document retrieval services over the period 2006-2011 at two libraries in Istanbul that serve the nursing and dentistry schools of two universities.
Keywords: Medical librarianship, e-documents, e-journals, document retrieval, article request, ILL.